Nutritional and morphological attributes of stay green vis-Ã -vis go-brown sorghumcultivars at different stages of maturity - SINGH, SULTAN; KATIYAR, D S; THEODOROU, M K; SAI PRASAD, S V; MISHRA, U S; BHASKAR, R B; PANDEY, K C; S VERMA, O P; MISHRA, A K (The Indian Journal of Animal Sciences, 2011)
Six stay green (SG) varieties (M 35–1, A 2267–2, SPV 1284, CSV 15 , GSS 2 and B 24) and four go brown (GB) varieties (IS 4859, HD 20, J Sel 10 and IS 2179) were evaluated for nutritional constituents, in vitro dry matter digestibility (IVDMD), morphological attributes, fodder yield and sugar contents at 5 different stages of maturity (50% flowering– 1st, physiological maturity–2nd, 20 days after physiological maturity–3rd, 40 days after physiological maturity–4th, and 60 days after physiological maturity–5th). The accumulation of dry matter (DM) in leaf of SG sorghum was significantly lower at initial 3 stages of growth. DM contents in stem part of SG cultivars were significantly lower than GB. Stem fraction of SG exhibited significantly lower ligno-cellulose contents compared to GB. NDF and ADF contents were 2–12 and 2–8 units lower in stem of SG than GB in different stages of crop maturity. Leaf width and leaf length was significantly higher in SG than GB at initial 3 stages of growth. Plant height was significantly higher in GB than SG cultivars. Numbers of dried leaves were lesser in SG than GB and increased with the advancing stage of maturity in both type of sorghum. IVDMD of stem part in SG was 3.0 to 9.5 unit more than GB across the growth stages. GFY yield was significantly higher in SG vis-à -vis GB at all stages of maturity, while sugar contents (% brix) were significantly more in SG than GB in stages after physiological maturity. SG and GB sorghum had maximum accumulation of sugar at third stage of crop growth. SG cultivars had more CP, low fibre with higher IVDMD, sugar contents and fodder yield than GB.